Election Practices In Ethiopia: An Overview - Dagnachew Tolessa, (Advances in Social Sciences Research Journal, 2019)
Democracy is a system of government or administration in which people (the governed people) have great role in deciding who to rule them and what kind of decision should be passed by the government. People play this role through different ways. Among these, one is through regular, free fair and democratic elections. This paper examines the concept and meaning of democratic elections in the case of Ethiopia and its relationship with democratic principles. The paper focuses on the Democratic Elections: a Case study in Ethiopia, mainly in the twentieth century. It tries to discuss the main features of Ethiopian elections that made in the country under different regimes of government that succeed each other in the twentieth Cuntury: Namely during the reign of Emperor Haile-Sellassie I(r. 1930-1974), the Dergue regime (1974-1991) and the current government (EPDRF regime, from 1991 to present). It also deals with the general historical views of elections in Ethiopia. It try to give the reader general picture of Ethiopian elections that had practiced overtime. In addition, by comparing one election practices with the other, this paper tries to show the progresses that the country tries to achieve. In writing this paper, I encountered serious shortage of written sources or literatures in relation to my topic. The scarcity of written materials obliged me to use internet sources as a means to engrave this paper. However, I tried my best in using other different literatures that are, in one way or another, related to the issue. Nevertheless, I tried to refer the limited available written materials I am able to found and I also used my own experience that I have got in my political life.